2018
DOI: 10.1615/intjmedmushrooms.2018025815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooking and In Vitro Digestion on Antioxidant Properties and Cytotoxicity of the Culinary-Medicinal Mushroom Pleurotus ostreatoroseus (Agaricomycetes)

Abstract: In this study we evaluated the antioxidant capacity, antimicrobial activity, and cytotoxicity of an aqueous extract of the Pleurotus ostreatoroseus mushroom, which was cooked. Fresh basidiocarps were heated and steamed at 100°C and the resulting aqueous extract was assessed before and after in vitro digestion. Cooking reduced the amounts of phenolic compounds in the extract. The antioxidant activity of the extract was evaluated through the use of 4 methods. The lowest half-maximal effective concentration (EC50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
2
0
6
Order By: Relevance
“…In their studies, incubation of Caco-2 cells with A. bisporus extracts resulted in decreased expression of cyclooxygenase-2 and prostaglandin F2α receptor as compared with the lipopolysaccharide (LPS) or TNF-α-activated cells. The antioxidant activity of Pleurotus ostreatoroseus (Agaricomycetes) mushroom was also noted by Brugnari et al [16].…”
Section: Antioxidant Activitiessupporting
confidence: 53%
See 1 more Smart Citation
“…In their studies, incubation of Caco-2 cells with A. bisporus extracts resulted in decreased expression of cyclooxygenase-2 and prostaglandin F2α receptor as compared with the lipopolysaccharide (LPS) or TNF-α-activated cells. The antioxidant activity of Pleurotus ostreatoroseus (Agaricomycetes) mushroom was also noted by Brugnari et al [16].…”
Section: Antioxidant Activitiessupporting
confidence: 53%
“…Mushrooms have been reported to have many useful functions including antitumor, anticancer, antihypertensive, cholesterol lowering effect, antioxidant properties, anti-inflammatory, immune-modulatory function, as well as anti-bacterial, antiviral, and antifungal activities on human and animal health [15,16].…”
Section: Biological Role Of Medicinal Mushroomsmentioning
confidence: 99%
“…In their tests, Caco-2 cell incubation with A. bisporus extracts resulted in declined prostaglandin F2α receptor expression and cyclooxygenase-2 compared to lipopolysaccharide (LPS) or TNF-α-activated cells. Brugnari et al (85) also noted antioxidant activity in the Pleurotus ostreatoroseus (Agaricomycetes) mushroom. Kumar et al (86) found that mushroom powder (1.2%) and 0.3% probiotics (Saccharomyces cerevisiae) in broiler diet improved the meat quality.…”
Section: Antioxidant Parametersmentioning
confidence: 97%
“…Исследования показали, что высшие базидиомицеты способны синтезировать широкий комплекс биологически активных веществ, таких как полисахариды, гликопротеины, терпены, стеролы, пигменты и др. [1][2][3][4][5][6], которые могут проявлять антибактериальные [2,[5][6][7], антивирусные [2,5,6,[8][9][10][11], противоопухолевые, антипаразитарные, иммуномодулирующие и другие свойства [2,6,10,12]. При этом указанные комплексы из базидиомицетов, как правило, не являются токсичными или малотоксичными для человека или животных [1,2,6,10,12].…”
Section: Introductionunclassified